Family relationships and non-resident black South African fathers’ contact with their adolescent children: a study of families with infrequent non-resident father-child contact - Nell, Erika (Stellenbosch : Stellenbosch University, 2023)
Thesis (PhD)--Stellenbosch University, 2023.